Nigella sativa oil on chronic constrictive injury (CCI) induced neuropathic pain of sciatic nerve in Wistar rats - Akhter, Masuma; Biswas, Parijat; Shahnaz, Monira; Rafiq, Kazi; Ali, Taskina (Journal of Bangladesh Society of Physiologist, 2024)
Background: Various adverse effects have been reported with conventional treatments of neuropathic pain. Nigella sativa (N. sativa), a medicinal herb, has been shown to possess several beneficiary effects. Objective: To assess the effects of N. sativa oil on neuropathic pain and ATP sensitive potassium channel (KATP) in Wistar rats. Methods: This experimental study was conducted on 120 Wistar rats (200±50gm). On the basis of treatments, all rats were grouped into Group I [normal control (NC) normal saline (NS) 5 ml/kg]; Group II [sham control (SC) {sham surgery + NS}], Group III [CCI control (CCIC) {Chronic constriction injury to sciatic nerve (CCI) + NS}]; Group IV [N. sativa oil experimental (NSOexp) {CCI + N.sativa (400 mg/kg)}], Group V [Glibenclamide experimental (Gliexp) {CCI + N. sativa (400 mg/kg) + glibenclamide (15 mg/kg)}] groups. Both the NSO and NS were administered orally once daily for consecutive 21 days and single dose of glibenclamide was given intraperitoneally on the day of experiment, to the respective rats. Then on the basis of neuropathic pain evaluation tests, all the groups were subdivided into ‘a’ [for sciatic functional index (SFI) in walking track analysis], ‘b’ [for tail flick latency (TFL) in cold tail immersion test], ‘c’ [for paw withdrawal threshold (PWT) in von Frey test], and ‘d’ (for rection time in hot plate test). The statistical analysis was done by one way ANOVA followed by Bonferroni post hoc test. Results: In this study, significantly (pd”0.001) higher SFI, TFL, PWT and reaction time were found in NSO exp rats when compared to those of CCIC rats. In addition, there were significant (pd”0.001) differences in the above-mentioned variables between rats of NSO exp group and Gliexp group. Conclusion: From the present study it might be concluded that, N. sativa prevents worsening of neuropathic pain in Wistar rats by blocking KATP channel. J Bangladesh Soc Physiol 2023;18(1): 35-45